2022
DOI: 10.1037/pas0001171
|View full text |Cite
|
Sign up to set email alerts
|

An item response theory analysis of two frequently used measures of identity development.

Abstract: Identity development—exploring options and making commitments—is an important process related to human functioning across the lifespan. An accurate understanding of identity development processes requires precise measures, but commonly used questionnaires have not been subject to intensive psychometric analyses. We investigated the psychometric properties of two such measures, the Utrecht Management of Identity Commitments Scale and the Dimensions of Identity Development Scale. Previous analyses have treated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Additionally, while our measurement invariance tests seemed to support invariance across waves, there were some analytic difficulties that may limit the reliability of this conclusion. Furthermore, the DIDS (and other identity process measures) has been critiqued as a measure that lacks statistical sensitivity, or the ability to accurately capture information about the intended underlying constructs (Johnson et al, 2022). Given that issues of sensitivity may limit the ability to detect change over time, this is a notable issue, but additional longitudinal research on this issue is needed.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Additionally, while our measurement invariance tests seemed to support invariance across waves, there were some analytic difficulties that may limit the reliability of this conclusion. Furthermore, the DIDS (and other identity process measures) has been critiqued as a measure that lacks statistical sensitivity, or the ability to accurately capture information about the intended underlying constructs (Johnson et al, 2022). Given that issues of sensitivity may limit the ability to detect change over time, this is a notable issue, but additional longitudinal research on this issue is needed.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…These tools are designed to evaluate different dimensions of identity, such as personal, relational, public, and collective aspects [38]. For example, Johnson et al measured participants' musical identity using the Musical Identity Measurement (MIM), which consists of four factors: musical calling, musical self-efficacy, emotional attachment, and growth mindset [39]. The study's results showed measurement invariance between male and female participants, supporting the concept of an individual's self-concept related to their musical activities [39].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, while our measurement invariance tests seemed to support invariance across waves, there were some analytic difficulties that may limit the reliability of this conclusion. Further, the DIDS (and other identity process measures) has been critiqued as a measure that lacks statistical sensitivity, or the ability to accurately capture information about the intended underlying constructs (Johnson et al, 2022). Given that issues of sensitivity may limit the ability to detect change over time, this is a notable issue, but additional longitudinal research on this issue is needed.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%